Refrigerant influence on performance of heat pump - M Ju Frolov; I K Shatalov; Ju A Antipov; D V Terekhov (RUDN Journal of Engineering Research, 2009)
Analysis of refrigerant influence on heat pump performance is given in this paper. Advantages of alternative refrigerants are shown.